Frankenstein, or, The Modern Prometheus - Shelley, Mary Wollstonecraft, 1797-1851.; Ward, Lynd, 1905-; Ruiz, Aristides (New York, N.Y. : Portland House Illustrated Classics, 1988)
A monster assembled by a scientist from parts of dead bodies develops a mind of his own as he learns to loathe himself and hate his creator.
Keywords: Monsters -- Fiction; Horror stories